Structure characterization of a polysaccharide extracted from noni (Morinda citrifolia L.) and its protective effect against DSS-induced bowel disease in mice. (May 2019) - Jin, Mingyu; Wang, Yuxiao; Yang, Xiaobing; Yin, Hui; Nie, Shaoping; Wu, Xiaoyong
Abstract: Inflammatory bowel disease (IBD), including Crohn's disease and ulcerative colitis, has gradually emerged as a public health challenge worldwide. Morinda citrifolia (noni) has been used to treat various ailments by Pacific Islanders for centuries. In this work, noni fruit polysaccharide (NFP) was obtained by hot water extraction, and its structure was initially explored. The molecular weight of NFP was approximately 456 kDa, and its monosaccharide components predominantly consisted of Gala (58.44%), Gal (4.44%), Glu (21.13%), Rha (4.84%), and Ara (2.16%) to form galacturonic acid, rhamnogalacturonan-I, arabinogalactan, and arabinan. The protective effect of NFP on the intestinal mucosal barrier was then investigated using DSS-induced IBD model mice. Whereas DSS treatment inhibited intestinal mucosal expression and destroyed the tight junction of epithelial cells, by contrast, NFP promoted mucosal and tight junction protein (zonula occludens-1 and occludin) expression. In conclusion, NFP improved the clinical diagnosis of acute colitis in IBD mice and may present a potential source of IBD treatment. Graphical abstract: NFP-Noni Fruit Polysaccharide. Image 1 Highlights: The NFP was a homogalacturonan type pectin with a backbone of linear (1 → 4)-linked- α -GalA p. The NFP could ameliorate the clinical symptoms of the IBD mice. The NFP could attenuated DSS-induced redistribution of ZO-1 and Occludin in colonic epithelial cells.